2002
DOI: 10.1053/euhj.2001.2712
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, controlled trial of integrated heart failure management. The Auckland Heart Failure Management Study

Abstract: Aims To determine the effect of an integrated heart failure management programme, involving patient and family, primary and secondary care, on quality of life and death or hospital readmissions in patients with chronic heart failure. Methods and ResultsThis trial was a cluster randomized, controlled trial of integrated primary/secondary care compared with usual care for patients with heart failure. The intervention involved clinical review at a hospital-based heart failure clinic early after discharge, individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
201
1
12

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(224 citation statements)
references
References 17 publications
(18 reference statements)
8
201
1
12
Order By: Relevance
“…The majority of studies related to patients with diabetes (n = 6; Simmons 2003; Nocon et al 2004;Smith et al 2004;Kirsh et al 2007;Borgermans et al 2009;Askew et al 2010;Goderis et al 2010;Jackson et al 2010). Three were from New Zealand (Doughty et al 2002;Pearl et al 2003;Rea et al 2004;Sheridan et al 2009), two each from Australia (Simmons 2003;Askew Jackson et al 2010;Jackson Tsai et al 2010) and the UK (Nocon et al 2004;Coast et al 2005;Salisbury et al 2005), with the remaining three from the US (Kirsh et al 2007), Belgium (Borgermans et al 2009;Goderis et al 2010) and Ireland (Smith et al 2004). One study was an RCT Salisbury et al 2005), four were cluster RCTs (Doughty et al 2002;Pearl et al 2003;Rea et al 2004;Smith et al 2004;Borgermans et al 2009;Goderis et al 2010), three reported a quasi-experimental design (Nocon et al 2004;Kirsh et al 2007;Askew et al 2010;Jackson et al 2010) and two used a pre-post design (Simmons 2003;Sheridan et al 2009).…”
Section: Study Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of studies related to patients with diabetes (n = 6; Simmons 2003; Nocon et al 2004;Smith et al 2004;Kirsh et al 2007;Borgermans et al 2009;Askew et al 2010;Goderis et al 2010;Jackson et al 2010). Three were from New Zealand (Doughty et al 2002;Pearl et al 2003;Rea et al 2004;Sheridan et al 2009), two each from Australia (Simmons 2003;Askew Jackson et al 2010;Jackson Tsai et al 2010) and the UK (Nocon et al 2004;Coast et al 2005;Salisbury et al 2005), with the remaining three from the US (Kirsh et al 2007), Belgium (Borgermans et al 2009;Goderis et al 2010) and Ireland (Smith et al 2004). One study was an RCT Salisbury et al 2005), four were cluster RCTs (Doughty et al 2002;Pearl et al 2003;Rea et al 2004;Smith et al 2004;Borgermans et al 2009;Goderis et al 2010), three reported a quasi-experimental design (Nocon et al 2004;Kirsh et al 2007;Askew et al 2010;Jackson et al 2010) and two used a pre-post design (Simmons 2003;Sheridan et al 2009).…”
Section: Study Detailsmentioning
confidence: 99%
“…Three were from New Zealand (Doughty et al 2002;Pearl et al 2003;Rea et al 2004;Sheridan et al 2009), two each from Australia (Simmons 2003;Askew Jackson et al 2010;Jackson Tsai et al 2010) and the UK (Nocon et al 2004;Coast et al 2005;Salisbury et al 2005), with the remaining three from the US (Kirsh et al 2007), Belgium (Borgermans et al 2009;Goderis et al 2010) and Ireland (Smith et al 2004). One study was an RCT Salisbury et al 2005), four were cluster RCTs (Doughty et al 2002;Pearl et al 2003;Rea et al 2004;Smith et al 2004;Borgermans et al 2009;Goderis et al 2010), three reported a quasi-experimental design (Nocon et al 2004;Kirsh et al 2007;Askew et al 2010;Jackson et al 2010) and two used a pre-post design (Simmons 2003;Sheridan et al 2009). Eight studies used quantitative methods (Doughty et al 2002;Pearl et al 2003;Simmons 2003;Rea et al 2004;Smith et al 2004;Coast et al 2005;Salisbury et al 2005;Kirsh et al 2007;Borgermans et al 2009;Askew et al 2010;Goderis et al 2010;Jackson et al 2010), whereas two used a mixed-methods approach …”
Section: Study Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies to improve adherence in several countries were successful regarding quality of therapy and reduction of readmissions. In these studies, heart failure patients underwent lessons during hospitalization 1-4 after discharge from the hospital, 5,6 were treated by an out-patient clinic specializing in heart failure, 7 -9 or by multidisciplinary interventions. 10,11 Hypothesizing that improving the knowledge of the disease would lead to better adherence, 12 reduce readmission, mortality, and thus probably reduce health costs, 13,14 we established the Vienna Heart School (VHS).…”
mentioning
confidence: 99%
“…In this context, according to Lynce 2007, 8 5% of chronically ill patients consumed 30% of inpatient costs in Portugal. With quality management it is possible to obtain values as significant as a 40% reduction in hospital admissions due to chronic respiratory diseases, 25% reduction in hospitalizations due to diabetes; 38% reduction in emergency calls to patients with asthma, [9][10][11][12] and 50% reduction in the occurrence of absenteeism due to arthritis. 13 Thus, our study aimed to evaluate the epidemiological profiles and total health care costs of a group of patients with CDNCD at a Brazilian supplementary health service that was monitored by a CDMCP.…”
mentioning
confidence: 99%